The Role of Institutions and Firm Heterogeneity for Labour Market Adjustment: Cross-Country Firm-Level Evidence - Peter Gál; Alexander Hijzen; Zoltan Wolf (Institute for the Study of Labor (IZA), 2013)
This paper investigates the role of policies and institutions for aggregate labour market dynamics during the recent financial crisis using firm-level data. First, it provides comparable estimates on firm-level labor adjustment by country, industry and firm size. Second, using variance decomposition methods, it shows that differences in firm-level labor adjustment accounts for about 40% of the cross-country variation in aggregate employment growth at the outset of the crisis. We interpret this as evidence that differences in institutional settings accounted for a substantial part of the variation in aggregate employment growth. Third, we find that stronger protection for regular workers is associated with lower (higher) employment (earnings-per-worker) response in the wake of output shocks. This suggests employment protection shifts the burden of adjustment from the extensive to the intensive margin. However, in explaining the diverse cross-country patterns in employment adjustment during the crisis, the impact of employment protection alone seems to be small.
Keywords: E24; J23; 330; labour market adjustment; employment protection; global financial crisis